A Novel Approach for HST Delays Using Pythagorean Fuzzy AHP and Regression Analysis - Hümeyra Bolakar Tosun (Advances in Civil Engineering)
The increased need for transportation worldwide has led to intense competition among several transportation types. Thus, considering factors affecting the choice of transportation means of passengers is essential. In many countries, railways have been losing market share in both freight and passenger transport, especially against highways. Railway transport systems must regain their declining share for the sake of the economy and sustainability. For this reason, many studies have been conducted to eliminate delays in high-speed trains, the speed of which is the most important criterion for preference. This study determines the reasons for train delays in a bid to make the high-speed train project successful in Turkey and for trains to serve better. Furthermore, regression analysis and the Pythagorean fuzzy analytic hierarchy process (AHP) analysis were performed according to the most effective criteria. The most effective criteria were determined as maintenance, repair, and closure due to renewal. Additionally, various suggestions regarding the effect of the obtained causes on train delays were put forward.